KAJIAN GEOMETRI JALAN ANGKUT TERHADAP KONSUMSI BAHAN BAKAR ALAT ANGKUT DUMP TRUCK PADA PENAMBANGAN BATU ANDESIT DI KABUPATEN KULON PROGO YOGYAKARTA - Gesang Winukir; Inmarlinianto Inmarlinianto; Eddy Winarno (Universitas Muhammadiyah Mataram, 2022)
CV. Muncul Karya is one of the andesite mines located in Sidomulyo Village, Pengasih District, Kulon Progo Regency, Yogyakarta Province. The mining process is carried out conventionally using the Komatsu PC-200 loading and unloading equipment and the Mitsubitshi Fuso SHD and Toyota Dyna 130 HT dump truck to the Crusher with a hauling distance of 7,75 km. The purpose of this study was to determine the factors that affect fuel consumption and to know the fuel ratio in Mitsubishi Fuso SHD and Toyota Dyna 130 HT. There are several things that affect the increase in fuel consumption, namely the workload of the equipment, the condition of the haul road geometry, road subsidence, and the distance of transportation from the mining front to the Crusher. Based on observations of actual working conditions, there is a haul road slope that exceeds the company's reference, which is 8% and the haul road condition still has more than 5 cm subsidence. Fuel consumption of Mitsubitshi Fuso SHD and Toyota Dyna 130 HT dump truck based fuel on rimpull calculations of 4,92 liters/hour and 5,56 liters/hour. The production of theory based on observations of the time of circulation of 5,03 tons/hour and 5,20 tons/hour. After repairing the slope of the transport road adjusted to the company's reference ≤ 8% and the condition of the transport road does not have a wheel load of more than 5 cm on the surface of the transport road. Fuel consumption for Mitsubishi Fuso SHD dump truck based on rimpull calculations is 4,73 liters/hour and production is 5,26 tons/hour, while fuel consumption for Toyota Dyna 130 HT dump truck based on rimpull calculations is 5,43 liters/hour and production to 5,50 tons/hour. So the fuel ratio is 0,90 liters/ton for Mitsubitshi Fuso SHD dump truck and 0,98 liters/ton for Toyota Dyna 130 HT dump truck.